2006
DOI: 10.1128/jvi.01773-05
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Hepatitis A Virus Infection by Small Interfering RNAs

Abstract: Infection by hepatitis A virus (HAV) can cause acute hepatitis and, rarely, fulminant liver failure, in particular in patients chronically infected with hepatitis C virus. Based on our previous observation that small interfering RNAs (siRNAs) can silence translation and replication of the firefly luciferase-encoding HAV replicon, we now exploited this technology to demonstrate the effect of siRNAs on viral infection in Huh-7 cells. Freshly and persistently infected cells were transfected with siRNAs targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 56 publications
2
39
0
1
Order By: Relevance
“…Aside from HIV-1, other human pathogens that have been targeted include poliovirus; hepatitis A, B, and C viruses; enteroviruses; coxsackievirus; rhinovirus; and influenza virus (3, 8, 10, 15, 17, 20-22, 25, 29, 30, 33, 40, 42, 43). Escape from transient siRNA treatment has been described for poliovirus (9,10), hepatitis C virus (42), and hepatitis A virus (20). These studies suggest that single point mutations can diminish or even abolish the RNAi effect.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Aside from HIV-1, other human pathogens that have been targeted include poliovirus; hepatitis A, B, and C viruses; enteroviruses; coxsackievirus; rhinovirus; and influenza virus (3, 8, 10, 15, 17, 20-22, 25, 29, 30, 33, 40, 42, 43). Escape from transient siRNA treatment has been described for poliovirus (9,10), hepatitis C virus (42), and hepatitis A virus (20). These studies suggest that single point mutations can diminish or even abolish the RNAi effect.…”
mentioning
confidence: 95%
“…These studies suggest that single point mutations can diminish or even abolish the RNAi effect. Repeated treatment with the same siRNA triggered the selection of multiple mutations in the viral target sequences, leading to increased levels of RNAi resistance (9,10,20,42).…”
mentioning
confidence: 99%
“…Interestingly, viral escape to RNAi can also occur by a point mutation outside the target sequence of siRNA, if this mutation changes local RNA folding into a structure that reduces the accessibility of the target sequence (Westerhout et al 2005). Several viruses have been reported to escape suppression by effective siRNAs, which include HIV-1, HCV, HAV, peste des petits ruminants virus (PPRV) and Poliovirus (von Eije et al 2008;Wilson & Richardson 2005;Kusov et al 2006;Gitlin et al 2005). Studies of HIV-1 and HBV populations have shown that many resistant mutants may pre-exist before they have been exposed to inhibitors and the siRNAs may also exert selection pressure on these pre-existing resistant mutants (Najera et al 1995;Wu et al 2005).…”
Section: Viral Escapementioning
confidence: 99%
“…Usually, the viral structural proteins or polymerases are targeted for silencing. Promising results have been reported against HIV (Novina et al 2002), Hepatitis A (Kusov et al 2006) and B (Shlomai & Shaul 2003) in humans and foot-and-mouth-disease virus in cattle (Chen et al 2006a). Several RNAi-based drugs for human diseases are currently in the pre-clinical development stage and phase I or II clinical trials (www.…”
Section: Rnai As a Therapeutic Toolmentioning
confidence: 99%